Recent results on mass measurements of exotic nuclides in storage rings. Issue 1 (January 2016) - Yan, X L; Blaum, K; Litvinov, Yu A; Tu, X L; Xu, H S; Zhang, Y H; Zhou, X H
Abstract: Storage ring mass spectrometry allows for simultaneous measurements of masses of a large amount of nuclides. Two measurement techniques, isochronous and Schottky mass spectrometry, are applied. The clear advantage of the storage ring mass spectrometry is that only a few particles are required to measure their mass with high accuracy. In this contribution we address the most recent results obtained at the two presently operating facilities, namely the Experimental Storage Ring (ESR) in Darmstadt and the Experimental Cooler-Storage Ring (CSRe) in Lanzhou.